Obesity Prolongs the Inflammatory Response in Mice After Severe Trauma and Attenuates the Splenic Response to the Inflammatory Reflex - Gärtner, Fabian; Gihring, Adrian; Roth, Aileen; Bischof, Joachim; Xu, Pengfei; Elad, Leonard; Wabitsch, Martin; Burster, Timo; Knippschild, Uwe (Frontiers in Immunology, 2021)
Thoracic traumas with extra-thoracic injuries result in an immediate, complex host response. The immune response requires tight regulation and can be influenced by additional risk factors such as obesity, which is considered a state of chronic inflammation. Utilizing high-dimensional mass and regular flow cytometry we define key signatures of obesity-related alterations of the immune system during the response to the trauma. In this context, we report a modification in important components of the splenic response to the inflammatory reflex in obese mice. Furthermore, during the response to trauma, obese mice exhibit a prolonged increase of neutrophils and an early accumulation of inflammation associated CCR2+CD62L+Ly6Chi monocytes in the blood, contributing to a persistent inflammatory phase. Moreover, these mice exhibit differences in migration patterns of monocytes to the traumatized lung, resulting in decreased numbers of regenerative macrophages and an impaired M1/M2 switch in traumatized lungs. The findings presented in this study reveal an attenuation of the inflammatory reflex in obese mice, as well as a disturbance of the monocytic compartment contributing to a prolonged inflammation phase resulting in fewer phenotypically regenerative macrophages in the lung of obese mice.